Review on Cloud Computing Security Challenges - Evans Osei Opoku; Rym Regaieg; Mohamed Koubaa (European Scientific Journal, ESJ, 2020)
In this paper, security issues associated with cloud computing are reviewed. Additionally, the types of cloud and service models have also been pointed out. Cloud computing has ruled the data innovation industry as of late. Giant data centersthat provide cloud services are been set up due to the global approval of cloud and virtualization innovations. Cloud computing is characterized as a web-based software service since Information Technology (IT) resources like network, server, storage, and so on are based on the Web. Along these lines, cloud computing services can be utilized at any place and whenever on the Personal Computer (PC) or smart mobile phones. In light of the on-demand, adaptable and versatile administration it can give, a considerable measure of companies that beforehand deployed locally has moved their organizations to the cloud. Although cloud computing brings a whole lot of advantages, many security challenges have been brought up to both cloud providers and clients.